The Revitalizing the Character of Mutual Cooperation Based on Lotisan Culinary Tradition in History Learning Practices - Roro Wilis; Dyah Kumalasari (Indonesian Values and Character Education Journal, 2025)
Lotisan is a peripheral culinary tradition that holds significant value in maintaining social cohesion within Javanese rural communities. Amid the growing tendency toward individualism in modern life, integrating local wisdom into formal education remains a crucial challenge. This study aims to analyze the meaning of the lotisan culinary tradition from the perspective of Javanese society, examine its integration into history learning through demonstration methods in the topic of prehistoric human life, and evaluate its implications for the development of students’ cooperation character. This research employed a qualitative approach with a single case study design. Data were collected through non participant observation, in depth interviews, document analysis, and literature review. The participants included school leaders, history teachers, students, and community representatives selected through purposive sampling. Data validity was ensured through triangulation techniques, and data were analyzed using an interactive model combined with content analysis to interpret both primary and secondary data.The findings indicate that lotisan functions as a form of social capital that strengthens cooperation and social solidarity. Its integration into history learning through contextual and project-based approaches creates interactive and meaningful learning experiences while reinforcing the internalization of cooperative values among students. This study concludes that local culinary traditions can serve as effective pedagogical media for character education. The implication is that history learning should utilize local wisdom as a contextual resource to foster not only cognitive development but also students’ character formation.